COMPARISON STUDY ON BEARING CAPACITY OF CIRCULAR AND DIAMOND HOLE LAMINATES UNDER SHEAR LOAD - GAO Wei; YAO XiongHua; ZHANG WenJun (Jixie qiangdu)
Based on the shear load case, the bearing capacity and failure mode of composite laminates with circular and diamond holes were studied by test and numerical simulation. The results show: under the premise of the same laminate weight, the same hole accessibility and the same stacking angle information, the load-carrying capacity of the laminate with diamond hole is greater than that of the laminate with circular hole; based on the nonlinear continuum damage mechanics（CDM）, the fiber damage is predicted by using the maximum strain failure criterion, and the matrix damage is predicted by using the three-dimensional nonlinear puck failure criterion A three-dimensional finite element model of laminate is established and numerical simulation is carried out. The comparison with the experimental results shows that the model can effectively predict the bearing capacity and failure mode of laminate with hole.